2018
DOI: 10.1089/fpd.2017.2390
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellaspp. and Extended-Spectrum Cephalosporin-ResistantEscherichia coliFrequently Contaminate Broiler Chicken Transport Cages of an Organic Production Company

Abstract: Antimicrobial resistant bacteria in retail meat pose a health hazard to the public, as does contamination of these products with Salmonella. Our aim was to determine the prevalence of Salmonella as well as Escherichia coli expressing AmpC and extended-spectrum beta-lactamase (ESBL) resistance phenotypes contaminating broiler transport cages and fresh, retail ground chicken meat. Sterile gauze sponges were used to collect duplicate cage floor samples from transport trailers that deliver market-ready birds to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, the amount of Salmonella on positive cages was higher, demonstrating that this process was ineffective. Previous studies have shown that transport cages can potentially act as a source of broiler exposure to Salmonella as they are transported into the food processing plants [21]. The prevalence in the carcasses is much higher to that in similar studies conducted in Colombia [22], Costa Rica [23], Canada [24], and the European Union [1].…”
Section: Discussionmentioning
confidence: 90%
“…However, the amount of Salmonella on positive cages was higher, demonstrating that this process was ineffective. Previous studies have shown that transport cages can potentially act as a source of broiler exposure to Salmonella as they are transported into the food processing plants [21]. The prevalence in the carcasses is much higher to that in similar studies conducted in Colombia [22], Costa Rica [23], Canada [24], and the European Union [1].…”
Section: Discussionmentioning
confidence: 90%
“…We acknowledge that conclusions based on food products should be interpreted with caution. Cross contaminations during processing and handling (Cohen Stuart et al, 2012;Mollenkopf et al, 2018) as well as the exposure of humans may influence the ESBL-PE prevalence. Overall, the stated potential contamination sources for organic products, while possible, require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Salmonella spp. presented a resistance profile against cephalosporins [33]. This indicates that during the transport of broilers, bacterial contamination is strongly associated with resistance to different antibiotics, which can compromise food safety [25,33].…”
Section: Bacterial Infection During Poultry Transportmentioning
confidence: 99%
“…presented a resistance profile against cephalosporins [33]. This indicates that during the transport of broilers, bacterial contamination is strongly associated with resistance to different antibiotics, which can compromise food safety [25,33]. To complicate the situation, multidrug-resistant strains of different bacteria can pose a risk of infection and spread to uninfected broiler chickens transported in the same crates [33].…”
Section: Bacterial Infection During Poultry Transportmentioning
confidence: 99%